A morphologic study on the effect of leg composition and muscularity of different protein and fiber levels in morkaraman male lambs - Ali Rıza Aksoy; Kadir Aslan (Eurasian Journal of Veterinary Sciences)
In this research, some of leg muscles (m, semitendinosus, m, semimarTtıranosus, m. adductor, m. glu-teobiceps, m, quadriceps lemoris, m, sartorius) ol lour groups ot 31 Morkaraman male lambs led with different protein and liber levels were dissected. The weights and lenghts ol dissected muscles were measured maximum circumference ol the muscles. In addition, muscles were removed also on lemur and tibia ve the weights, lenghts and circumlerence ol corpus were measured, From lour groups were compared muscle, bone, cold carcass, leg, leg muscles, leg latts and leg bones weights. There were no significant difference among groups, statistically; but there was an increase of muscle and bone weights, with the increase of protein levels on diets and was a decrease of lemur and tibia weights, with the decrease of fiber levels.